KEPASTIAN HUKUM TERHADAP AKTA JUAL BELI TANAH YANG DIBUAT PPAT DILUAR DAERAH KERJANYA SERTA AKIBAT HUKUMNYA - Yolanda, Berlian; Chandra, Tofik Yanuar; Halim, Anriz Nazaruddin (Case Law : Journal of Law, 2025)
The Land Deed Making Official (PPAT) is personally responsible for carrying out his duties and position in every deed making. This research aims to 1) the legal consequences of land sale and purchase deeds made by land deed making officials outside their work area and 2) legal certainty regarding sale and purchase deeds made by land deed making officials outside their work area using Soeroso's theory of legal consequences and Jan Michiel Otto's theory of legal certainty. The research method uses normative juridical. The research uses a statutory approach, case approach, analytical approach, and conceptual approach with types and sources of legal materials including primary and secondary. Data analysis techniques use systematic interpretation, grammatical interpretation and analogy legal construction techniques. Based on the research results, it can be concluded that basically the sanctions that can be imposed on PPATs who violate the PPAT Position Regulations or other statutory regulations are warnings, warnings, temporary dismissal, honorable dismissal, dishonorable dismissal. PPAT can be dishonorably dismissed. The Deed of Sale and Purchase issued by PPAT is a deed that is legally flawed because it does not comply with applicable procedures or regulations. The PPAT which made the AJB was not signed at the PPAT office because it was clear and clear that the AJB was legally flawed; The mistake made by PPAT was carrying out its obligations and duties carelessly and carelessly. As a public official with high dignity, he is required to always be careful and careful in carrying out every task and obligation he carries out. PPAT should be more careful and careful in issuing AJB.